Проницаемость слизистой полости рта при многоформной экссудативной эритеме - Почтарь, В.Н.; Деньга, Э.М.; Шнайдер, С.А. (Актуальні проблеми транспортної медицини, 2017)
Показано, что у пациентов с многоформной экссуадативной эритемой наблюдалась высокая проницаемость десны для красителя раствора Шиллера-Писарева и, следовательно, микроорганизмов, а также наблюдалось существенное прокрашивание десны в области длин волн 620-700 нм, связанное с реакцией йодного раствора с резервным полисахаридом гликогеном. Проведенные лечебно-профилактические мероприятия с использованием базовой терапии и комплекса интерферон+солкосерил привели в основной группе пациентов со сниженной реактивностью к определённому усилению барьерной защиты слизистой десны, особенно на участке, прилегающем к зубу, и к значительному уменьшению степени воспаления в десне, о чём свидетельсвует увеличение коэффициента отражения света в области 660 нм как по переходной складке (на 18%), так и на участках десны, прилегающих к зубу (на 21%). Показано, що у пацієнтів із многоформною ексудативною еритемою спостерігалися висока проникність ясен для барвника розчину Шилера-Писарєва і, отже, мікроорганізмів, а також істотне профарбовування ясен в області довжин хвиль 620-700 нм, пов’язане з реакцією йодного розчину з резервним полісахаридом глікогеном. Проведені лікувальнопрофілактичні заходи з використанням базової терапії і комплексу інтерферон + солкосерил призвели в основній групі пацієнтів зі зниженою реактивністю до певного посилення бар’єрного захисту слизової ясен, особливо на ділянці, що прилягає до зуба, і до значного зменшення ступеня запалення в яснах, про що свідчить збільшення коефіцієнта відбиття світла в області 660 нм як по перехідній складці (на 18%), так і на ділянках ясен, що прилегають до зуба (на 21%). In the literature, there is practically no quantitative information on the impact of exudative erythema multiforme on the permeability of the periodontal tissues and barrier protection against the infiltration of various microorganisms. The purpose of the work was a quantitative spectrocolorimetry evaluation of gums permeability for colorant in the treatment of exudative erythema multiforme. Patients of comparison group (12 persons) received only basic therapy includes chelators, antihistamines and desensitizing agents, capillary protector and a local anesthetic, antiseptic and proteolytic preparations. Patients of basic group (12 people) in addition to basic therapy received preventive complex include interferon and solkoseril injections by the scheme, as well as the elixir “Lizomukoid” and mucosal gel “Kvertulin”. Spectro colorimetric study an oral cavity mucous for a colorant permeability were performed according to the method [6]. Perfomed therapeutic and preventive measures with the use of basic and complex therapy of interferon + solkoseril led to a certain strengthening of the gums mucous barrier protection, especially in the area surrounding the tooth, and a significant reduction in the degree of inflammation.